Changing of Magnetic Flux Density Distribution in a Squirrel-Cage Induction Motor with Broken Rotor Bars - Vaimann, T.; Belahcen, A.; Kallaste, A. (Elektronika ir Elektrotechnika, 2014)
This paper presents the finite element modelling of three-phase squirrel-cage induction motor with broken rotor bar faults. Finite element model based on a real machine is constructed, propagation of broken rotor bar fault and its influence on the magnetic flux density distribution of the machine cage is observed. As the propagation of the fault will result in total breakdown of the induction machine rotor, if the fault is not detected and solved, necessity of condition monitoring is pointed out. Analysis of the fault and its affect to the magnetic field in the rotor cage as well as changes in the phase voltage spectrum are presented. DOI: http://dx.doi.org/10.5755/j01.eee.20.7.8018